Design and Development of Self-Emulsifying Drug Delivery Systems of Tolvaptan - Madhuri, D. (Asian Journal of Pharmaceutics (AJP), 2023)
Tolvaptan, a selective vasopressin receptor antagonist, is a poorly soluble drug. It is used to treat hyponatremia. To solve the solubility problem and enhance bioavailability, a novel approach of self-emulsifying drug delivery systems was used. These are isotropic mixtures of oil, surfactants, and cosurfactants, when they contact with the GI fluid spontaneously produce fine oil-in-water emulsion and are subsequently absorbed into lymphatic pathways, bypassing the first-pass hepatic effect. Cinnamon oil and orange oil were used as oils, Tween 80, Tween 60, and Tween 20 were used as surfactants and propylene glycol, poly ethylene glycol 400, and ethanol are used as cosurfactants for the formulation and there by evaluated. The droplet sizes are in ranges of 37.8–176 μm and PDI value is 0.271. The zeta potential value is −1.6 mV and the amount of drug release is that 81.50% was observed in F5 formulation. It conclude that the self-micro emulsifying drug delivery system is suitable for Tolvaptan drug to improve the drug release and there by bioavailabilty.